Cloud Computing and Security Challenges: A Comprehensive Review of Modern Amazon Web Services Solutions - Aditya Gedam,; Jeetendra Singh Yadav, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Cloud computing has revolutionized the IT industry by offering scalable, cost-effective, and flexible solutions for data storage, processing, and application deployment. Amazon Web Services (AWS), as a leading cloud service provider, has played a pivotal role in advancing cloud technologies. However, with the widespread adoption of cloud platforms, significant security challenges have emerged, including data breaches, unauthorized access, and compliance concerns. This paper provides a comprehensive review of modern AWS solutions addressing these challenges. It explores AWS's robust security architecture, including identity and access management (IAM), encryption techniques, threat detection systems, and compliance tools. Additionally, the paper analyzes best practices for securing cloud workloads and mitigating vulnerabilities in AWS environments. Through a detailed examination of current trends, case studies, and emerging technologies, this review offers insights into how AWS continues to enhance its security measures to meet evolving threats. The findings aim to guide IT professionals, organizations, and researchers in understanding and leveraging AWS for secure and resilient cloud computing infrastructures.
Keywords: Cloud Computing; Amazon Web Services (AWS); Cloud Security; Data Protection; dentity and Access Management (IAM); Encryption; Threat Detection; Compliance; Secure Cloud Infrastructure; Cybersecurity Challenges